2012
DOI: 10.1089/hum.2011.121
|View full text |Cite
|
Sign up to set email alerts
|

Silencing of miR20a Is Crucial for Ngn1-Mediated Neuroprotection in Injured Spinal Cord

Abstract: MicroRNAs (miRNAs) compose a relatively new discipline in biomedical research, and many physiological processes in disease have been associated with changes in miRNA expression. Several studies report that miRNAs participate in biological processes such as the control of secondary injury in several disease models. Recently, we identified novel miRNAs that were abnormally up-regulated in a traumatic spinal cord injury (SCI). In the current study, we focused on miR20a, which causes continuing motor neuron degene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(49 citation statements)
references
References 41 publications
2
47
0
Order By: Relevance
“…This suggests that miR-21 expression in the hippocampus may affect multiple components of TBI pathophysiology. miR20a may cause continuing motor neuron degeneration when overexpressed in spinal cord injury (SCI) (71). Blocking miR20a in SCI animals effectively induces definitive motor neuron survival and neurogenesis, and improves the functional deficit.…”
Section: Traumatic Injurymentioning
confidence: 99%
“…This suggests that miR-21 expression in the hippocampus may affect multiple components of TBI pathophysiology. miR20a may cause continuing motor neuron degeneration when overexpressed in spinal cord injury (SCI) (71). Blocking miR20a in SCI animals effectively induces definitive motor neuron survival and neurogenesis, and improves the functional deficit.…”
Section: Traumatic Injurymentioning
confidence: 99%
“…Several therapeutic approaches have been used to improve the microenvironment of the injured spinal cord and/or to stimulate the endogenous repair in an attempt to ameliorate secondary injury 9, 11, 13, 14. Although a majority of studies has focused on compounds with neuroprotection against secondary injury in SCI, their therapeutic efficacy remains controversial 15.…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that miRNAs could regulate Notch signaling. Moreover, recent studies have also shown that Drosha and miR-20 regulates the expression of neurogenin [21,22], suggesting the regulatory effects of miRNAs on pancreas development.…”
Section: Mirna-regulated Signaling Pathways In Pancreas Developmentmentioning
confidence: 97%